The Reception of the Book of Poems "Fardel de eisilado" in Galicia of the Interior and of the Outside from the Unpublished Correspondence of Luís Seoane - Fraguas Vidal, Rafael (Madrygal. Revista de Estudios Gallegos, 2015)
This analysis of the correspondences between Luís Seoane and the Galician intellectuals of the interior as of the exile puts of relay the key points of the reception of his book of poems Fardel de eisilado: the realistic social esthetics of the poems, the effort for the language and the important paper of the correspondence that allowed to our poet-painter to give to know his work in the exile and return in a certain way to the world intellectual Galician of the interior.